IMPROVEMENT IN EFFICIENCY OF AIR PREHEATER IN BOILER TPS- 1 EXPANSION - Sudhakar, S.; Raguraman, C.M. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
An air pre-heater is a general term to describe any device designed to heat air before another process (for example, combustion in a boiler) with the primary objective of increasing the thermal efficiency of the process. They may be used alone or to replace a recuperative heat system or to replace a steam coil. In particular, this project describes the combustion air pre-heaters used in large boilers found in thermal power stations producing electric power from e.g. fossil fuels, biomasses or waste. The purpose of the air preheater is to recover the heat from the boiler flue gas which increases the thermal efficiency of the boiler by reducing the useful heat loss of the flue gas in an regenerative pre-heater. This project analysis how operation parameters of an regenerative air preheater can be optimized in order to increase its efficiency and consequently the overall efficiency of a boiler. For this purpose, the RAPH in thermal power station -1 expansion at neyveli is considered and studied for a period and suitable remedies have been suggested.